Development of a Diagnostic Test for Student Misconception Detection of Coordination System Material Using Four-Tier Multiple Choice - Pratama, Riandy; Indriyanti, Dyah Rini; Mindyarto, Budi Naini (Journal of Innovative Science Education)
This study is the development of diagnostic test instrument four tier multiple choice to detect student misconceptions on the system material of human coordination. The diagnostic test is carried out on students who have received the coordination system material. The purpose of this study is to analyze diagnostic test validity and to analyze the profile of students' misconceptions on the material of the coordination system using four-tier multiple choices. This research is a Research and Development (R&D) with the 4D method, namely definite, design develop and Disseminate. The subjects of this research are the students of XII IPA 1, 2, and 3 at SMAN 1 Terusan Nunyai and the students of XII IPA 3, 4, and 5 at SMAN 1 Terbanggi Besar. The result of this research shows a valid question instrument with a CVR value is 0.80 and CVI value is 0.78 with 8 examiners and 35 items of questions. The profile of misconceptions at SMAN 1 Terusan Nunyai in the excellent class is 10.69%, medium class is 30.57% and low class is 40.86% who experienced misconceptions, while at SMAN 1 Terbanggi Besar, the category of excellent class is 26.94%, medium class is 32.12% and low class is 27.48%. The conclusion of this research is there are many students who experience misconceptions on the coordination system material in the nervous system and hormones.